The ambassadors : America's diplomats on the front lines - Richter, Paul (Paul R.) (Simon & Schuster, 2019)
The State Department<U+2019>s heroes are the front-line diplomats who have been unheralded, but crucial in the line of national defense for two decades of wars in the Middle East. In The Ambassadors, Paul Richter shares the astonishing, true-life stories of four expeditionary diplomats who “do the hardest things in the hardest places.” We<U+2019>ll see Ryan Crocker<U+2019>s effort to organize a new Afghan government after the fall of the Taliban, even threatening the life of a Pashtun warlord, a US ally, to ensure that a column of tanks could join US forces in the biggest battle of the Afghan war. Robert Ford, the sole American official for the province of Najaf in central Iraq, tries to restart the economy and deal with growing militia violence<U+2014>and is taken hostage by a Shia militia. In Syria, he is chased by government thugs for defying the country<U+2019>s ruler. J. Christopher Stevens is smuggled into Libya as U.S. Envoy to the rebels during its bloody civil war, then returns as ambassador only to be killed during a terror attach in Benghazi. War-zone veteran Anne Patterson is sent to Pakistan, considered the world<U+2019>s most dangerous country, to broker deals that prevent a government collapse and to help guide the secret war on jihadists.